Development of geomodel for concentration determination of hazardous chemicals in the atmosphere - Thamer, Khudhair Abed (Eastern-European Journal of Enterprise Technologies, 2018)
A critical analysis of the approaches to the development of a model for determining the concentration of hazardous chemicals (HC) in the atmosphere, which are the basis of computeraided environmental monitoring systems (CEMS) has been carried out. It has been established that the lack of effective functioning of the existing CEMS is determined by the imperfection of the models used to determine the concentration of atmospheric chemical concentration in the atmosphere. In addition, the organic disadvantage of such systems is their departmental affiliation and, as a result, the limited number of potential users. To improve the efficiency of the discussed class of systems, a concept of integrated use has been proposed, within the CEMS framework, elements of information and analytical systems for environmental monitoring, satellite image processing tools, geoinformation technologies, and also mathematical software for calculating the concentration of various types of atmospheric HCs. Building a CEMS based on this concept will provide an opportunity to significantly improve the efficiency of their functioning in the aspects of reducing the time for making decisions, as well as reducing the risk of making wrong decisions. The mathematical support of the CEMS is based on the “Gaussian” statistical model of HC emission, and is intended, along with geographic information technologies, to synthesize a geomodel of groundlevel atmosphere pollution by HCs. As an illustrative example, the situation of the release of chemical waste in the area of Bila Tserkva (Kyiv region, Ukraine) is considered. Theoretical results form the methodological basis for the implementation of the applied information technology for the creation, deployment and operation of a decision support system for eliminating the consequences of an emergency situation caused by the proliferation of chemical water in the atmosphere